The Influence of Functional Fitness and Cognitive Training of Physical Disabilities of Institutions - I-Chen Yeh; Chia-Ming Chang; Ko-Chia Chen; Wei-Chin Hong; Yu-Hsiung Lu (The Scientific World Journal)
According to an investigation done by Taiwan Ministry of the Interior in 2013, there was more than 90% of the disability care institutions mainly based on life care. Previous studies have shown that individuals can effectively improve physical and cognitive training, improved in independent living and everyday competence. The purpose of the study was to investigate influence of the intervention program applying functional fitness and cognitive training to disabled residents in the institution. The subjects were disabled persons of a care institution in southern Taiwan and were randomly divided into training and control groups, both having 17 subjects. The age of the subjects was between 56 and 98 years with a mean age of 79.08 ± 10.04 years; the subjects of training group implemented 12 weeks of training on physical and cognitive training, while the control group subjects did not have any training program. The results revealed that subjects of the training group have significantly improved their functional shoulder rotation flexibility of left and right anterior hip muscle group flexibility of right, sitting functional balance of left and right, naming, attention, delayed recall, orientation, and Montreal cognitive assessment (MOCA). The study suggested developing physical fitness programs and physical and cognitive prescriptions for the disabled people of the institutions.